Knowledge, attitudes, and practices of healthcare professionals on oral care of pregnant women in Brunei Darussalam - Nur-Afifah Syafiqah Muhammad-Safwan; Khadizah H. Abdul-Mumin; Hanif Abdul Rahman; Rafidah Gharif; Haji-Mohin Haji-Momin; Ramlah Kisut; Ruth Zielinski; Jagjit Singh Dhaliwal (BDJ Open, 2023)
Abstract Objective To examine nationwide the knowledge, attitudes, and practices of healthcare professionals on oral/dental care of pregnant women in Brunei Darussalam. Materials and methods A descriptive cross-sectional study conducted using an online survey of eligible healthcare professionals in all Government Maternal and Child Health Care Clinics, Dental Clinics and Obstetrics and Gynecological Clinics in four hospitals covering the whole of Brunei Darussalam. Participants were given seven days to complete the survey. Sub-group analysis using Chi-square test for independence and one-way Analysis of Variance (ANOVA) was used to determine the significant association between domains of oral care practices and demographic factors. P values less than 0.05 was considered statistically significant. Results A total of 346 healthcare professionals participated in this online study. Most participants (94.3%) responded that they perceived oral health to be of high importance. However, less than two thirds of the participants (59.0%) included oral health questions during antenatal health assessments. Moreover, only 16.2% of participants frequently discussed the importance of oral care with their antenatal patients. Conclusions In this survey, most healthcare professionals viewed oral health to be of high importance for prenatal/antenatal patients. However, not all put those views into practice with regard to oral care in pregnant women.